Electrochemistry of active chromium, part IV: Dissolution of chromium in deaerated sulfuric acid - Dražić Dragutin M.; Popić Jovan P.; Jegdić B.; Vasiljević-Radović D. (Journal of the Serbian Chemical Society, 2004)
Chromium dissolution in aqueous sulfuric acid solutions in the pH range 0.5 –3 was studied electrochemically by the potentiostatic or very slow potentiodynamic method, and by the analyses of the Cr ion concentrations in the electrolyte formed during the experiments. It was shown that the electrochemical anodic dissolution follows a common Tafel line with a slope of ca. 120 mVdec-1, independent of the solution pH and the hydrodynamics while the passivation potentials and passivation currents were independent on hydrodynamics but strongly dependent on the pH. In parallel with the electrochemical dissolution, a considerable "anomalous" or chemical Cr dissolution process occurs, as evidenced by the spectrophotometric analyses of the electrolytes for Cr ions after prolonged potentiostating of the electrodes at different potentials, as well as by measuring the electrode weight losses. All these results indicate the existence of a potential independent reaction of Cr dissolution occurring in parallel to the anodic dissolution process. Mechanisms for both the electrochemical and the chemical process are proposed. The consequences of these phenomena on the behavior of some practical systems where chromium or a chromium alloy (e.g., stainless steels) are used are discussed.